In the Monoid_ZF_1 theory we consider multiplicities of \(n\cdot x\) of monoid elements, i.e. special cases of expressions of the form \(x_1\oplus x_2\oplus\dots\oplus x_n\) where \(x_i=x\) for \(i=1..n\). In the group context where we usually use multiplicative notation this translates to the "power" \(x^n\) where \(n\in \mathbb{N}\), see also section "Product of a list of group elements" in the Group_ZF theory. In the group setting the notion of raising an element to natural power can be naturally generalized to the notion of raising an element to an integer power.
The integer power is defined in terms of natural powers of an element and its inverse. In this section we study properties of expressions \((x^n)\cdot(x^{-1})^k\), where \(x\) is a group element and \(n,k\) are natural numbers.
The natural power of \(x\) multiplied by the same power of \(x^{-1}\) cancel out to give the neutral element of the group.
lemma (in group0) nat_pow_inv_cancel:
assumes \( n\in nat \), \( x\in G \)
shows \( x^{n}\cdot (x^{-1})^{n} = 1 \)proofThe natural power of \(x^{-1}\) multiplied by the same power of \(x\) cancel out to give the neutral element of the group. Same as nat_pow_inv_cancel written with \(x^{-1}\) instead of \(x\).
lemma (in group0) nat_pow_inv_cancel1:
assumes \( n\in nat \), \( x\in G \)
shows \( (x^{-1})^{n}\cdot x^{n} = 1 \)proofIf \(k\leq n\) are natural numbers and \(x\) an element of the group, then \(x^n\cdot (x^{-1})^k = x^(k-n)\).
lemma (in group0) nat_pow_cancel_less:
assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( x^{n}\cdot (x^{-1})^{k} = x^{n - k} \)proofIf \(k\leq n\) are natural numbers and \(x\) an element of the group, then \((x^{-1})^n\cdot x^k = (x^{-1})^(k-n)\).
lemma (in group0) nat_pow_cancel_less1:
assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( (x^{-1})^{n}\cdot x^{k} = (x^{-1})^{n - k} \)proofIf \(k\leq n\) are natural numbers and \(x\) an element of the group, then \(x^k\cdot (x^{-1})^n = (x^{-1})^(k-n)\).
lemma (in group0) nat_pow_cancel_more:
assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( (x^{-1})^{k}\cdot x^{n} = x^{n - k} \)proofIf \(k\leq n\) are natural numbers and \(x\) an element of the group, then \((x^{-1})^k\cdot x^n = x^{(k-n)}\).
lemma (in group0) nat_pow_cancel_more1:
assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( x^{k}\cdot (x^{-1})^{n} = (x^{-1})^{n - k} \)proofIn this section we introduce notation basic properties of integer power in group context. The goal is to show that the power homomorphism property: if \(x\) is an element of the group and \(n,m\) are integers then \(x^{n+m}=x^n\cdot x^m\).
We extend the group0 context with some notation from int0 context. Since we inherit the multiplicative notation from the group0 context the integer "one" is denoted \( 1 _Z \) rather than just \( 1 \) (which is the group's neutral element).
locale group_int0 = group0 +
defines \( \mathbb{Z} \equiv int \)
defines \( a + b \equiv IntegerAddition\langle a,b\rangle \)
defines \( - a \equiv \text{GroupInv}(\mathbb{Z} ,IntegerAddition)(a) \)
defines \( a - b \equiv a + ( - b) \)
defines \( 0 \equiv \text{ TheNeutralElement}(\mathbb{Z} ,IntegerAddition) \)
defines \( 1 _Z \equiv \text{ TheNeutralElement}(\mathbb{Z} ,IntegerMultiplication) \)
defines \( \mathbb{Z} ^+ \equiv \text{Nonnegative}(\mathbb{Z} ,IntegerAddition,IntegerOrder) \)
defines \( m \leq n \equiv \langle m,n\rangle \in IntegerOrder \)
defines \( a \lt b \equiv a\leq b \wedge a\neq b \)
Next define notation for the integer power \( x^{z} \). The difficulty here is that in ZF set theory nonnegative integers and natural numbers are different things. So, we use the notion of zmagnitude defined in the standard Isabelle/ZF Int theory. For an integer number \(z\), \( | z|_N \) is like absolute value of \(z\) but interpreted as a natural number. Hence, we define the integer power \( x^{z} \) as \(x\) raised to the magnitude of \(z\) if \(z\) is nonnegative or \(x^{-1}\) raised to the same natural power otherwise.
definition (in group_int0)
\( x^{z} \equiv (\text{if } 0 \leq z\text{ then }x\text{ else }x^{-1})^{| z|_N } \)
An integer power of a group element is in the group.
lemma (in group_int0) powz_type:
assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z} \in G \) using assms, zmagnitude_type, nat_mult_type, inverse_in_group unfolding powz_defA group element raised to (integer) zero'th power is equal to the group's neutral element. An element raised to (integer) power one is the same element.
lemma (in group_int0) int_power_zero_one:
assumes \( x\in G \)
shows \( x^{ 0 } = 1 \) and \( x^{1 _Z} = x \) using assms, Int_ZF_1_L8A(1), int_ord_is_refl1, zmag_zero_one, nat_mult_zero, Int_ZF_2_L16A(1), nat_mult_one unfolding powz_defIf \(x\) is an element of the group and \(z_1,z_2\) are nonnegative integers then \(x^{z_1+z_2}=x^{z_1}\cdot x^{z_2}\), i.e. the power homomorphism property holds.
lemma (in group_int0) powz_hom_nneg_nneg:
assumes \( 0 \leq z_1 \), \( 0 \leq z_2 \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \) using assms, add_nonneg_ints(1,2), nat_mult_add unfolding powz_defIf \(x\) is an element of the group and \(z_1,z_2\) are negative integers then the power homomorphism property holds.
lemma (in group_int0) powz_hom_neg_neg:
assumes \( z_1 \lt 0 \), \( z_2 \lt 0 \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \) using assms, neg_not_nonneg, add_neg_ints(1,2), inverse_in_group, nat_mult_add unfolding powz_defWhen the integers are of different signs we further split into cases depending on which magnitude is greater. If \(x\) is an element of the group and \(z_1\) is nonnegative, \(z_2\) is negative and \(|z_2|\leq |z_1|\) then the power homomorphism property holds. The proof of this lemma is presented with more detail than necessary, to show the schema of the proofs of the remaining lemmas that we let Isabelle prove automatically.
lemma (in group_int0) powz_hom_nneg_neg1:
assumes \( 0 \leq z_1 \), \( z_2 \lt 0 \), \( \left| z_2 \right|_N \leq \left| z_1 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)proofIf \(x\) is an element of the group and \(z_1\) is nonnegative, \(z_2\) is negative and \(|z_1|<|z_2|\) then the power homomorphism property holds.
lemma (in group_int0) powz_hom_nneg_neg2:
assumes \( 0 \leq z_1 \), \( z_2 \lt 0 \), \( \left| z_1 \right|_N \lt \left| z_2 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \) using assms, add_nonneg_neg2, neg_not_nonneg, leI, nat_pow_cancel_more1 unfolding powz_defIf \(x\) is an element of the group and \(z_1\) is negative, \(z_2\) is nonnegative and \(|z_1|\leq |z_2|\) then the power homomorphism property holds.
lemma (in group_int0) powz_hom_neg_nneg1:
assumes \( z_1 \lt 0 \), \( 0 \leq z_2 \), \( \left| z_1 \right|_N \leq \left| z_2 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \) using assms, add_neg_nonneg1, nat_pow_cancel_more, neg_not_nonneg unfolding powz_defIf \(x\) is an element of the group and \(z_1\) is negative, \(z_2\) is nonnegative and \(|z_2| < |z_1|\) then the power homomorphism property holds.
lemma (in group_int0) powz_hom_neg_nneg2:
assumes \( z_1 \lt 0 \), \( 0 \leq z_2 \), \( \left| z_2 \right|_N \lt \left| z_1 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \) using assms, add_neg_nonneg2, neg_not_nonneg, leI, nat_pow_cancel_less1 unfolding powz_defThe next theorem collects the results from the above lemmas to show the power homomorphism property holds for any pair of integer numbers and any group element.
theorem (in group_int0) powz_hom_prop:
assumes \( z_1\in \mathbb{Z} \), \( z_2\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)proofA group element raised to power \(-1\) is the inverse of that group element.
lemma (in group_int0) inpt_power_neg_one:
assumes \( x\in G \)
shows \( x^{ - 1 _Z} = x^{-1} \) using assms, neg_not_nonneg, neg_one_less_zero, zmag_opposite_same(2), Int_ZF_1_L8A(2), zmag_zero_one(2), inverse_in_group, nat_mult_one unfolding powz_defIncreasing the (integer) power by one is the same as multiplying by the group element.
lemma (in group_int0) int_power_add_one:
assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z + 1 _Z} = x^{z}\cdot x \) using assms, Int_ZF_1_L8A(2), powz_hom_prop, int_power_zero_one(2)For integer power taking a negative of the exponent is the same as taking inverse of the group element.
lemma (in group_int0) minus_exp_inv_base:
assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{ - z} = (x^{-1})^{z} \)proofInteger power of a group element is the same as the inverse of the element raised to negative of the exponent.
lemma (in group_int0) minus_exp_inv_base1:
assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z} = (x^{-1})^{ - z} \)proofThe next context is like group_int0 but adds the assumption that the group operation is commutative (i.e. the group is abelian).
locale abgroup_int0 = group_int0 +
assumes isAbelian: \( P \text{ is commutative on } G \)
In abelian groups taking a nonnegative integer power commutes with the group operation. Unfortunately we have to drop to raw set theory notation in the proof to be able to use int0.Induction_on_int from the abgroup_int0 context.
lemma (in abgroup_int0) powz_groupop_commute0:
assumes \( 0 \leq k \), \( x\in G \), \( y\in G \)
shows \( (x\cdot y)^{k} = x^{k}\cdot y^{k} \)proofIn abelian groups taking a nonpositive integer power commutes with the group operation. We could use backwards induction in the proof but it is shorter to use the nonnegative case from powz_groupop_commute0.
lemma (in abgroup_int0) powz_groupop_commute1:
assumes \( k\leq 0 \), \( x\in G \), \( y\in G \)
shows \( (x\cdot y)^{k} = x^{k}\cdot y^{k} \)proofIn abelian groups taking an integer power commutes with the group operation.
theorem (in abgroup_int0) powz_groupop_commute:
assumes \( z\in \mathbb{Z} \), \( x\in G \), \( y\in G \)
shows \( (x\cdot y)^{z} = x^{z}\cdot y^{z} \)proofFor any integer \(n\) the mapping \(x\mapsto x^n\) maps \(G\) into \(G\) and is a homomorphism hence an endomorphism of \((G,P)\).
theorem (in abgroup_int0) powz_end:
assumes \( n\in \mathbb{Z} \)
defines \( h \equiv \{\langle x,x^{n}\rangle .\ x\in G\} \)
shows \( h:G\rightarrow G \), \( \text{Homomor}(h,G,P,G,P) \), \( h \in \text{End}(G,P) \)proofThe mapping \(\mathbb{Z}\ni n\mapsto (x\mapsto x^n\in G)\) maps integers to endomorphisms of \((G,P)\).
theorem (in abgroup_int0) powz_maps_int_End:
shows \( \{\langle n,\{\langle x,x^{n}\rangle .\ x\in G\}\rangle .\ n\in \mathbb{Z} \} : \mathbb{Z} \rightarrow \text{End}(G,P) \) using powz_end(3), ZF_fun_from_totalassumes \( x\in G \)
shows \( x^{-1}\in G \)assumes \( n\in nat \), \( x\in G \)
shows \( x^{n + 1} = x^{n}\cdot x \) and \( x^{n + 1} = x\cdot x^{n} \)assumes \( n\in nat \), \( x\in G \)
shows \( n\cdot x \in G \)assumes \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\oplus b\oplus (c\oplus d) = a\oplus (b\oplus c)\oplus d \)assumes \( x\in G \)
shows \( x\cdot x^{-1} = 1 \wedge x^{-1}\cdot x = 1 \)assumes \( n\in nat \) and \( P(0) \) and \( \forall k\in nat.\ P(k)\longrightarrow P(k + 1) \)
shows \( P(n) \)assumes \( n\in nat \), \( x\in G \)
shows \( x^{n}\cdot (x^{-1})^{n} = 1 \)assumes \( a\in G \)
shows \( a = (a^{-1})^{-1} \)assumes \( n\in nat \), \( k\leq n \)
shows \( k\in nat \)assumes \( n\in nat \), \( m\in nat \), \( x\in G \)
shows \( (n + m)\cdot x = n\cdot x \oplus m\cdot x \)assumes \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot (b\cdot c) = a\cdot b\cdot c \)assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( x^{n}\cdot (x^{-1})^{k} = x^{n - k} \)assumes \( n\in nat \), \( x\in G \)
shows \( (x^{-1})^{n}\cdot x^{n} = 1 \)assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( (x^{-1})^{k}\cdot x^{n} = x^{n - k} \)assumes \( z\in \mathbb{Z} \)
shows \( z\leq z \)assumes \( x\in G \)
shows \( 1\cdot x = x \)assumes \( 0 \leq z_1 \), \( 0 \leq z_2 \)
shows \( 0 \leq z_1 + z_2 \), \( \left| z_1 + z_2 \right|_N = \left| z_1 \right|_N + \left| z_2 \right|_N \), \( z_1 + z_2 = \$\!\#\! (\left| z_1 \right|_N + \left| z_2 \right|_N ) \)assumes \( m \lt 0 \)
shows \( \neg ( 0 \leq m) \)assumes \( z_1 \lt 0 \), \( z_2 \lt 0 \)
shows \( z_1 + z_2 \lt 0 \), \( \left| z_1 + z_2 \right|_N = \left| z_1 \right|_N + \left| z_2 \right|_N \), \( z_1 + z_2 = \ \$\!-\!(\$\!\#\!(\left| z_1 \right|_N + \left| z_2 \right|_N )) \)assumes \( 0 \leq z_1 \), \( z_2 \lt 0 \), \( \left| z_2 \right|_N \leq \left| z_1 \right|_N \)
shows \( 0 \leq z_1 + z_2 \), \( \left| z_1 + z_2 \right|_N = \left| z_1 \right|_N - \left| z_2 \right|_N \), \( z_1 + z_2 = \$\!\#\!(\left| z_1 \right|_N - \left| z_2 \right|_N ) \)assumes \( 0 \leq z_1 \), \( z_2 \lt 0 \), \( \left| z_2 \right|_N \leq \left| z_1 \right|_N \)
shows \( 0 \leq z_1 + z_2 \), \( \left| z_1 + z_2 \right|_N = \left| z_1 \right|_N - \left| z_2 \right|_N \), \( z_1 + z_2 = \$\!\#\!(\left| z_1 \right|_N - \left| z_2 \right|_N ) \)assumes \( 0 \leq z_1 \), \( z_2 \lt 0 \), \( \left| z_1 \right|_N \lt \left| z_2 \right|_N \)
shows \( z_1 + z_2 \lt 0 \), \( \left| z_1 + z_2 \right|_N = \left| z_2 \right|_N - \left| z_1 \right|_N \), \( z_1 + z_2 = \ \$\!-\!(\$\!\#\!(\left| z_2 \right|_N - \left| z_1 \right|_N )) \)assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( x^{k}\cdot (x^{-1})^{n} = (x^{-1})^{n - k} \)assumes \( z_1 \lt 0 \), \( 0 \leq z_2 \), \( \left| z_1 \right|_N \leq \left| z_2 \right|_N \)
shows \( 0 \leq z_1 + z_2 \), \( \left| z_1 + z_2 \right|_N = \left| z_2 \right|_N - \left| z_1 \right|_N \), \( z_1 + z_2 = \$\!\#\!(\left| z_2 \right|_N - \left| z_1 \right|_N ) \)assumes \( z_1 \lt 0 \), \( 0 \leq z_2 \), \( \left| z_2 \right|_N \lt \left| z_1 \right|_N \)
shows \( z_1 + z_2 \lt 0 \), \( \left| z_1 + z_2 \right|_N = \left| z_1 \right|_N - \left| z_2 \right|_N \), \( z_1 + z_2 = \ \$\!-\!(\$\!\#\!(\left| z_1 \right|_N - \left| z_2 \right|_N )) \)assumes \( n\in nat \), \( k\leq n \), \( x\in G \)
shows \( (x^{-1})^{n}\cdot x^{k} = (x^{-1})^{n - k} \)assumes \( z_1\in \mathbb{Z} \), \( z_2\in \mathbb{Z} \)
shows \( ( 0 \leq z_1 \wedge 0 \leq z_2) \vee (z_1 \lt 0 \wedge z_2 \lt 0 ) \vee \) \( ( 0 \leq z_1 \wedge z_2 \lt 0 \wedge \left| z_2 \right|_N \leq \left| z_1 \right|_N ) \vee \) \( ( 0 \leq z_1 \wedge z_2 \lt 0 \wedge \left| z_1 \right|_N \lt \left| z_2 \right|_N ) \vee \) \( (z_1 \lt 0 \wedge 0 \leq z_2 \wedge \left| z_1 \right|_N \leq \left| z_2 \right|_N ) \vee \) \( (z_1 \lt 0 \wedge 0 \leq z_2 \wedge \left| z_2 \right|_N \lt \left| z_1 \right|_N ) \)assumes \( 0 \leq z_1 \), \( 0 \leq z_2 \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)assumes \( z_1 \lt 0 \), \( z_2 \lt 0 \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)assumes \( 0 \leq z_1 \), \( z_2 \lt 0 \), \( \left| z_2 \right|_N \leq \left| z_1 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)assumes \( 0 \leq z_1 \), \( z_2 \lt 0 \), \( \left| z_1 \right|_N \lt \left| z_2 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)assumes \( z_1 \lt 0 \), \( 0 \leq z_2 \), \( \left| z_1 \right|_N \leq \left| z_2 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)assumes \( z_1 \lt 0 \), \( 0 \leq z_2 \), \( \left| z_2 \right|_N \lt \left| z_1 \right|_N \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)assumes \( z\in \mathbb{Z} \)
shows \( | z|_N = \left| \ \$\!-\!z \right|_N \), \( | z|_N = \left| - z \right|_N \)assumes \( z_1\in \mathbb{Z} \), \( z_2\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z_1 + z_2} = x^{z_1}\cdot x^{z_2} \)assumes \( x\in G \)
shows \( x^{ 0 } = 1 \) and \( x^{1 _Z} = x \)assumes \( z\in \mathbb{Z} \)
shows \( 0 \lt z \vee z= 0 \vee z \lt 0 \)assumes \( 0 \lt z \)
shows \( ( - z) \lt 0 \)assumes \( x\in G \)
shows \( x^{ 0 } = 1 \) and \( x^{1 _Z} = x \)assumes \( z \lt 0 \)
shows \( 0 \lt ( - z) \)assumes \( m\in \mathbb{Z} \)
shows \( ( - m) \in \mathbb{Z} \)assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{ - z} = (x^{-1})^{z} \)assumes \( m\in \mathbb{Z} \)
shows \( ( - ( - m)) = m \)assumes \( a\in G \), \( b\in G \)
shows \( a\cdot b \in G \)assumes \( m \leq n \)
shows \( m \ \$\!\leq\ n \), \( m\in \mathbb{Z} \), \( n\in \mathbb{Z} \)assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z + 1 _Z} = x^{z}\cdot x \)assumes \( P \text{ is commutative on } G \) and \( a\in G \), \( b\in G \), \( c\in G \), \( d\in G \)
shows \( a\cdot (b\cdot c)^{-1} = (a\cdot d^{-1}\cdot c^{-1})\cdot (d\cdot b^{-1}) \), \( a\cdot b\cdot (c\cdot d) = c\cdot a\cdot (b\cdot d) \), \( a\cdot b\cdot (c\cdot d) = a\cdot c\cdot (b\cdot d) \), \( a\cdot (b\cdot c^{-1})\cdot d = a\cdot b\cdot d\cdot c^{-1} \), \( (a\cdot b)\cdot (c\cdot d)^{-1}\cdot (b\cdot d^{-1})^{-1} = a\cdot c^{-1} \)assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z} \in G \)assumes \( i\leq k \) and \( Q(i) \) and \( \forall m.\ i\leq m \wedge Q(m) \longrightarrow Q(m + 1 ) \)
shows \( Q(k) \)assumes \( m \leq n \)
shows \( m \ \$\!\leq\ n \), \( m\in \mathbb{Z} \), \( n\in \mathbb{Z} \)assumes \( z\in \mathbb{Z} \), \( x\in G \)
shows \( x^{z} = (x^{-1})^{ - z} \)assumes \( a\in G \) and \( b\in G \)
shows \( b^{-1}\cdot a^{-1} = (a\cdot b)^{-1} \)assumes \( k \leq 0 \)
shows \( 0 \leq ( - k) \)assumes \( 0 \leq k \), \( x\in G \), \( y\in G \)
shows \( (x\cdot y)^{k} = x^{k}\cdot y^{k} \)assumes \( z\in \mathbb{Z} \)
shows \( 0 \leq z \vee z\leq 0 \)assumes \( k\leq 0 \), \( x\in G \), \( y\in G \)
shows \( (x\cdot y)^{k} = x^{k}\cdot y^{k} \)assumes \( \forall x\in X.\ b(x) \in Y \)
shows \( \{\langle x,b(x)\rangle .\ x\in X\} : X\rightarrow Y \)assumes \( f:X\rightarrow Y \), \( x\in X \) and \( f = \{\langle x,b(x)\rangle .\ x\in X\} \)
shows \( f(x) = b(x) \) and \( b(x)\in Y \)assumes \( z\in \mathbb{Z} \), \( x\in G \), \( y\in G \)
shows \( (x\cdot y)^{z} = x^{z}\cdot y^{z} \)assumes \( n\in \mathbb{Z} \)
defines \( h \equiv \{\langle x,x^{n}\rangle .\ x\in G\} \)
shows \( h:G\rightarrow G \), \( \text{Homomor}(h,G,P,G,P) \), \( h \in \text{End}(G,P) \)